Republic - assisted house project for people in social rehabilitation process - Rollm, Mônica Grant; Barbosa, Saulo Jardim; Blum, Rodrigo; Carrozzo, Nelson Luiz Magalhães; Miguel, Maria Paula Cauchíck; Pandjiarjian, Cristina; Petri, Renata; Verdini, Flávio (Revista de Terapia Ocupacional da Universidade de São Paulo, 2000)
This paper intends to transform the six year experience "REPUBLICS" daily life in contribution for the reflection in mental health. More specifícally the one concern noninstitucionalization, desinstitucionalization and social rehabilitation.